2020
DOI: 10.1021/acs.macromol.0c00377
|View full text |Cite
|
Sign up to set email alerts
|

9,9-Dimethyl Dihydroacridine-Based Organic Photocatalyst for Atom Transfer Radical Polymerization from Modifying “Unstable” Electron Donor

Abstract: Organic photocatalytic atom transfer radical polymerization (ATRP) has recently become a research highlight. Organic photocatalysts based on phenothiazine, phenoxazine, and phenazine have been reported and exhibited remarkable performance. All of those structures contain two heteroatoms, which makes the oxidative state (i.e., the radical cation) of the photocatalysts stable enough to complete the catalytic cycle. However, despite the similar structure, 9,9-dimethyl dihydroacridine (DHA) was rarely used for con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…46 This is in contrast to acridine, which has been widely used for photo- or photoredox catalysts for cationic and radical polymerizations. 47–50…”
Section: Introductionmentioning
confidence: 99%
“…46 This is in contrast to acridine, which has been widely used for photo- or photoredox catalysts for cationic and radical polymerizations. 47–50…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we found that the D−A type organic photosensitizer can effectively transfer electrons to the substrate and catalyze polymerizations [10] . Similarly, we speculated that one‐dimensional organic D−A conjugated polymers can also efficiently catalyze redox reactions.…”
Section: Methodsmentioning
confidence: 83%
“…demonstrated 9,9‐dimethyl dihydroacridine as a potential PC in O‐ATRP. By substituting the PC′s active sites with required substituents, a functional structure‐property relationship was established, which helped synthesize the DPDHA‐P2F2 derivative as PC for efficient O‐ATRP [68] . Various other photocatalysts are also found suitable for O‐ATRP, including the derivatives of thienothiophene [69] and carbazoles [70] .…”
Section: Organic Photocatalystsmentioning
confidence: 99%
“…By substituting the PC's active sites with required substituents, a functional structure-property relationship was established, which helped synthesize the DPDHA-P2F2 derivative as PC for efficient O-ATRP. [68] Various other photocatalysts are also found suitable for O-ATRP, including the derivatives of thienothiophene [69] and carbazoles. [70] All the organic compounds discussed so far have a robust reduction potential in their excited state and an adequate excited-state lifetime, enabling them to mediate the polymerization through oxidative quenching mechanism.…”
Section: Classification Of O-atrp Photocatalysts Operating Via Oxidatmentioning
confidence: 99%
See 1 more Smart Citation